Differentiated Learning Strategies: Creating an Adaptive and Inclusive Indonesian Classroom - Nugrahani , Farida; Nurnaningsih, Nurnaningsih; Saputra, Eka Candra (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
Differentiated Differentiated learning strategies play an important role in Indonesian language subjects at the elementary school level. This study aims to describe: (1) the implementation of differentiated learning strategies in Indonesian language learning; (2) supporting factors in their implementation; (3) obstacles encountered; and (4) solutions adopted by teachers to overcome challenges in the implementation of differentiated learning strategies in Grade V of SD Negeri 1 Pare Mondokan Sragen, Central Java. The research method employed is descriptive qualitative with a case study approach. Primary data were obtained through classroom observations, in-depth interviews with teachers, students, and parents, as well as documentation. Secondary data consisted of lesson plans and teaching materials. A purposive sampling technique was applied, focusing on Grade V teachers, students, and parents actively involved in learning activities. The validity of the data was tested through source and method triangulation, while the data were analyzed using an interactive model consisting of data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of differentiated learning strategies in Grade V has made a significant contribution to improving students’ comprehension, particularly by accommodating diverse learning styles in Indonesian language subjects. This success was supported by initial diagnostic assessments, the use of simple technologies, and collaboration between teachers and parents. However, challenges remain in terms of limited resources and teachers’ readiness to manage heterogeneous classrooms. Solutions undertaken include strengthening teacher training, optimizing the use of technology, and enhancing communication with parents.